Cohort study: "Outcomes of kidney transplantation in patients with prosthetic heart valves". (19th October 2021) - Ouahmi, Hajar; Moceri, Pamela; Zorzi, Kevin; Albano, Laetitia; Durand, Matthieu; Karimi, Fatimaezzahra; Morelon, Emmanuel; Buron, Fanny; Le Quintrec, Moglie; Pernin, Vincent; Ladriere, Marc; Girerd, Sophie; et al.
Summary: The number of kidney transplant candidates with prosthetic heart valves (PHVs) is increasing. Yet, outcomes of kidney transplantation in these patients are still unclear. This is the first report of post‐transplant outcomes in patients with PHVs at time of kidney transplantation. We conducted a matched cohort study among recipients from the multicentric and prospective DIVAT cohort to compare the outcomes in patients with left‐sided PHVs at time of transplantation and a group of recipients without PHV matched according to age, dialysis time, initial disease, pretransplant DSA, diabetes, and cardiovascular events. Of 23 018 patients, 92 patients with PHVs were included and compared to 276 patients without PHV. Delayed graft function and postoperative bleeding occurred more frequently in patients with PHVs. Kidney graft survival was similar between groups. 5‐year overall survival was 68.5% in patients with PHV vs. 87.9% in patients without PHV [HR, 2.72 (1.57–4.70), P = 0.0004]. Deaths from infection, endocarditis, and bleeding were more frequent in patients with PHV. Mechanical valves, but not bioprosthetic valves, were independent risk factors for mortality [HR, 2.89 (1.68–4.97), P = 0.0001]. Patients with PHV have high mortality rates after kidney transplantation. These data suggest that mechanical valves, but not biological valves, increase risks of post‐transplant mortality. Abstract : Patients with PHV have high mortality rates after kidney transplantation. Mechanical valves, but not biological valves increase risks of post‐transplant mortality.